2018
DOI: 10.1080/24740527.2018.1471325
|View full text |Cite
|
Sign up to set email alerts
|

Developing a measure of distress-promoting parent behaviors during infant vaccination: Assessing reliability and validity

Abstract: Background: Infants rely on their parents' sensitive and contingent soothing to support their regulation from pain-related distress. However, despite being of potentially equal or greater import, there has been little focus on how to measure distress-promoting parent behaviors. Aims: The goal of this article was to develop and validate a measure of distress-promoting parent behaviors for acute painful procedures (e.g., vaccinations) that could be used by researchers and clinicians. Methods: Following initial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Parent distress-promoting behaviors were assessed using a checklist of observable distress-promoting behaviors with established validity and reliability in a vaccination context [ 18 ]. The checklist examines the presence of eight suboptimal or insensitive parent behaviors: (1) fathom wrong (i.e., making comments toward the distressed infant that either do not address, or discredit the infant’s distress, such as saying “It’s not so bad”), (2) face cover (i.e., covering the distressed infant’s face with any object such as a hand or blanket), (3) fashion first (i.e., dressing a distressed infant with no attempt to soothe the infant), (4) forceful (i.e., handling the infant roughly), (5) frustration (i.e., any facial expressions that reflect irritation with the infant’s distress, such as rolling eyes or sighing), (6) fearful (i.e., any parental facial expression that suggests they are scared or frightened), (7) flit away (i.e., any behavior or parental positioning that does not bring the infant close to the parent when the infant is distressed), and (8) flat face (i.e., a complete lack of emotional expression in response to the infant’s distress).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Parent distress-promoting behaviors were assessed using a checklist of observable distress-promoting behaviors with established validity and reliability in a vaccination context [ 18 ]. The checklist examines the presence of eight suboptimal or insensitive parent behaviors: (1) fathom wrong (i.e., making comments toward the distressed infant that either do not address, or discredit the infant’s distress, such as saying “It’s not so bad”), (2) face cover (i.e., covering the distressed infant’s face with any object such as a hand or blanket), (3) fashion first (i.e., dressing a distressed infant with no attempt to soothe the infant), (4) forceful (i.e., handling the infant roughly), (5) frustration (i.e., any facial expressions that reflect irritation with the infant’s distress, such as rolling eyes or sighing), (6) fearful (i.e., any parental facial expression that suggests they are scared or frightened), (7) flit away (i.e., any behavior or parental positioning that does not bring the infant close to the parent when the infant is distressed), and (8) flat face (i.e., a complete lack of emotional expression in response to the infant’s distress).…”
Section: Methodsmentioning
confidence: 99%
“…Whether this pattern holds for infant pain-related distress is unclear. Although previous research involving infant samples seems to suggest strong relationships with distress-promoting parent behaviors [ 18 ], and significant but small relationships with coping-promoting (e.g., emotional availability [ 13 , 14 , 15 ] and proximal soothing [ 6 , 8 , 9 , 10 ]) behaviors, these behaviors were not examined concurrently, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Introduction/Aim : Previous studies have shown strong relationships between infant pain-related distress and parents’ use of insensitive behaviors post-vaccination. 1 , 2 The present study explored predictors of parents’ insensitive behavior in response to infant pain-related distress, focusing on parent psychopathology, parenting stress, pre-needle worry, and pre-needle physiological arousal, as well as infant pre-needle distress.…”
Section: Predictors Of Parents’ Insensitive Behaviors In Response To Infant Vaccination Painmentioning
confidence: 99%